Qualidade ambiental das habitações de interesse social nos bairros Sol Nascente e Canaã II em Ituiutaba/MG - Ferreira, Leilaine de Fátima (2016)
The research aims to analyze the environmental quality of cluster housing set of social interest Sol Nascente and Canaã II built respectively by BNH and PMCMV in the city of Ituiutaba / MG. Justified primarily for its social and environmental relevance, because geography allows a deepening of studies linking urban environment and health through space and subjective analysis, as well as the need for solutions proposition for the environmental and social problems originating in appropriation of man on the natural environment. Therefore, we followed four methodological procedures: literature review; data collection (documentary research, direct observation and questionnaire); preparation of maps, cartograms, graphs and tables; and analysis of the environmental quality of Cluster housing Sol Nascente and Canaã II. It was found that although the population has realized the dream of home ownership in periods and different programs, the non execution of works of infrastructure and implementation of basic services are considered essential elements of damage to environmental quality of cluster housing, as well as their own attitudes of residents who contribute to the impairment of the environment.